Implikasi Model Double Loop Problem Solving Terhadap Kemampuan Berpikir Spasial Peserta Didik pada Materi Sistem Pencernaan - Ulfa Fauzi; Aa Juhanda; Billyardi Ramdhan (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
The aimed of this research is to analyze the influence of the double loop problem solving (DLPS) model on students' spatial reasoning abilities in digestive system subjects. The research used a quasi-experiment with a non-equivalent control group design. SMAN 1 Ciemas students' ability to think spatially is the variable that is measured. Research was led in two classes on the subject of the digestive system in the even semester of the 2022/2023 academic year. Before being handed over to students, all questions are validated by experts and then used with the help of research applications to find research results. The research data was tested for normality and homogeneity and finally the research hypothesis was tested using the Mann-Whitney test. The results of the research show that the DLPS model can influence students' spatial thinking abilities in class XI digestive system material at SMAN 1 Ciemas. In conclusion, the DLPS learning model with students' spatial thinking abilities can be an effective solution to face the progress of 21st century education. Keywords: Spatial Thinking Ability, Double Loop Problem Solving Model (DLPS), Students, Digestive System